Multicultural Education In Islamic Education Philosophy Perspective - Saiful Bahri (ISTAWA, 2020)
Multicultural education, a very strategic approach, is developed in the life of Indonesian society which has a variety of patterns in religion, ethnicity, ethnicity, and customs, all of which aim to live together in equality, strengthen and unite in the unity of the Unitary State of the Republic of Indonesia. In the concept of Islam, it also teaches multicultural education, so on this basis, the researcher wants to examine in depth how the idea of multicultural education is in the view of the philosophy of Islamic knowledge. This research uses a type of literature study research, the data which is the centre of this study is collected through variable data that is based on the writings, thoughts and opinions of figures and experts who talk about multiculturalism and the philosophy of Islamic education. This research results in a multicultural view that refers to the level of Islamic education that respects, appreciates and embraces all forms of diversity, tolerance, deliberation, cooperation and sharing so that it can be expected that people grow inequality seeing all forms of diversity to avoid fellow conflict.Pendidikan multikultural sebuah pendekatan yang sangat strategis dikembangkan dalam kehidupan bermasyarakat Indonesia yang bercorak beragam dalam agama, etnis, suku, adat istiadat yang tujuan semuanya itu untuk hidup bersama-sama dalam kesetaraan, memperkokoh serta mempersatukan dalam kesatuan Negera Kesatuan Republik Indonesia. Dalam konsep Islam pun mengajarkan tentang pendidikan multikultural, maka atas dasar ini peneliti ingin mengkaji secara mendalam bagaimana konsep pendidikan multikultural dalam pandangan filsafat pendidikan Islam. Penelitian ini menggunakan jenis penelitian studi pustaka, data yang menjadi pusat studi ini dikumpulkan melalui data variabel yang bertumpu pada tulisan, pemikiran, dan pendapat para tokoh dan pakar yang berbicara tentang multikultural dan filsafat Pendidikan Islam. Penelitian ini menghasilkan dalam pandangan multikultural yang mengacu pada tataran pendidikan Islam yang saling menghormati, menghargai dan merangkul semua bentuk keanekaragaman, bertoleransi, bermusyawarah, gotong royong dan saling berbagi, sehingga dengan demikian dapat diharapkan bagi masyarakat tumbuh dalam kesetaraan melihat segala bentuk keberagaman agar terhindar dari konflik sesama.